The effects of Environmental, Social, and Governance (ESG) scores on firm values in ASEAN member countries - Paulina Inggita Prabawati; Isna Putri Rahmawati (Accounting Department, Faculty of Business and Economics, Universitas Islam Indonesia, 2022)
This study examines the effect of Environmental, Social, and Governance (ESG) scores on firm value in ASEAN. This study uses data from 184 public companies listed on the stock exchanges of each country from 2010 to 2019. This study finds that ESG scores have a negative effect on firm value (Tobin's Q). This finding shows that the higher the ESG value, the lower the firm value (undervalued) in ASEAN. Furthermore, this study shows the influence of each pillar, namely the environmental, social, and governance. The environmental and social pillars negatively affect firm value, while the governance pillar has no effect. In ASEAN, a high ESG score is not considered an advantage for a company. This research has implications for companies to consider increasing information and compliance with environmental and social aspects of the company to increase their values. In addition, it also adds to the literature regarding the determinants of firm value on non-financial factors.